Understanding Familial DNA: National Study of Policies, Procedures, and Potential Impact, 2014 - Debus-Sherrill, Sara ([Verlag nicht ermittelbar], 2018)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. Seeking to measure the usage of Familial DNA Searching (FDS) to aid in criminal investigations, this study utilized a multi-phase, mixed methods approach to obtain data on FDS policies and practices in the United States. This study includes data from the National Survey of CODIS Laboratories, which was compiled after two expert roundtables, a literature and policy scan of practice, cost modeling, and state case studies. The study includes one SPSS data file: FDS_National_Survey_of_CODIS_Labs_Data.sav